A COMPARATIVE STUDY OF URBAN DIVISIONS BETWEEN LUOYANG CITY IN HAN AND WEI DYNASTIES AND ROME CITY IN IMPERIAL PERIOD - Jin Lipeng (International Journal of Innovative Technologies in Social Science, 2020)
The author of this article briefly analyzes the layout and division of Luoyang and Roman cities during the Han and Wei Dynasties from a historical perspective, and explores the characteristics and traditional craftsmanship of ancient buildings in the East and the West from a comparison.